Ultra Personal Computer. - Snoonian, Deborah (Architectural Record, 2004)
This Windows XP-compatible computer boasts the number-crunching power of a conventional laptop at a fraction of the size and weight. The ultra Personal Computer (uPC)comes equipped with a 1-gigahertz processor, a 20-gigabyte hard drive, a color display screen, and Firewire and Bluetooth wireless capabilities. A USB port lets you add a mouse or another peripheral device. When connected to its docking cable, the uPC can be enhanced with audio and Ethernet functions or a second USB or FireWire port. Though it's not souped-up enough to manipulate CAD files, the uPC represents a viable option for those who want to tote more power than a handheld organizer offers, but with a lot less bulk than a laptop.